Recycling Palm Shell Waste into Biochar Using Biomass-Based Pyrolysis Method for Sustainable Energy Transition: A Review - Setiawan, Naswa Mevira; Sella Stephanie; Aziz, Annisa Nazilatul; Berliana Yusfinda (Journal of Clean Technology, 2025)
Palm kernel shell (PKS), a by-product of Indonesia's palm oil industry, represents both a waste management challenge and an opportunity for renewable energy transition. This review critically examines recent advancements in the conversion of PKS into biochar using biomass-based pyrolysis. By synthesizing findings across multiple studies, the review highlights how pyrolysis parameters—such as temperature (200–1200 °C), residence time (1–4 hours), and chemical activation (NaOH, H₂SO₄)—affect the physicochemical properties of biochar. Among these, the combination of 550 °C pyrolysis temperature, 2-hour residence time, and NaOH pre-treatment via microwave-assisted pyrolysis was identified as optimal for maximizing fixed carbon content, surface area, and adsorption capacity. Such biochar is suitable for a wide range of applications, including soil amendment, wastewater treatment, and long-term carbon sequestration. The review not only confirms the environmental viability of PKS biochar based on Indonesian National Standards (SNI), but also emphasizes its role in supporting sustainable agriculture and mitigating greenhouse gas emissions. Future research directions include scaling production technologies and assessing biochar performance in diverse agroecological systems.